HASIL TANGKAPAN IKAN SELUANG BATANG (RASBORA ARGYROTAENIA BLKR 1850) BERDASARKAN UMUR BULAN (MOON AGE) DI SUNGAI BARITO KALIMANTAN SELATAN - Erwin Rosadi (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This study aims to obtain scientific data related to the effect of the moon age to R.argyrotaenia fish catches in the river Barito South Kalimantan. The method used in the study is the experimental fishing by fishing operations when the full moon and deadmoon, and to confirm the significance of the effect of different fish catches by using analysis of variance (Anova). The research results showed that the catches at the time ofthe operation in the full moon of 20.2 + 0.8 kg (68% of total catches) while catches in the dead moon of operation time of 9.5 + 0.2 kg (32 % of total catches). Results of Anova analysis showed that the value of F group (12.286) > F group at the level of error 5%(4.60), indicating that different groups have real impact on the amount of fish catches or reject H0. Value of F replications (1.20) < F replications at the level of error 5 % (2.48), indicating that the different treatment did not significantly affect the number of fishcatches or accept H0. The conclusion of this study is the number of fish caught during fishing operations in the full moon more than fishing operations at the time in the deadmoon.